The Impact Of A Proposed Training Program For The Development Of Special Endurance Depending On The Fatigue Index Of Defense And Attack Players - Kadraoui, Brahim (sports creativity, 2025)
The study aimed to find out the effectiveness of the use of a training program for the development of the special endurance (strength endurance and speed endurance) and find out the extent of its effectiveness in delay the onset of fatigue or get rid of the effects for the soccer players, and try to show the differences in fatigue between footballers index) defensive players and offensive), while the research sample was selected intentional manner of players Sports Academy as much as the number at 20 players, divided into two groups,) with each group of 05 players for the defense and 05 players made up the attack(. Then apply a training program for the development of the adjectives maintain speed endurance and Strength endurance, where the program included 24 training module for )02) two months, (03) servings a week, we have been testing effort anaerobic (RAST), The results concluded that the presence of significant differences between tribal and dimensional measurements of the two groups and in favor of the dimensional measurements, and in favor of the group that underwent the proposed program, and its efficiency among the defensive players and offensive .